Globalizing India how global rules and markets are shaping India's rise to power - Sinha, Aseema 1966- (New York Cambridge University Press, 2016)
"Over the course of the past two decades, India has undergone an enormous transformation which has fascinated many scholars, global leaders and interested observers. In 1990, India was a closed economy and a hesitant and isolated economic power. In 2015, however, India has rapidly risen on the global economic stage; foreign trade now drives more than half of the economy and Indian multi-nationals actively pursue global alliances. Focusing on second-generation reforms of the late 1990s, Aseema Sinha explores what facilitated this rapid change in a self-reliant country predisposed to nationalist ideas. Drawing on fieldwork undertaken in Geneva, New Delhi and Washington DC, alongside a close analysis of the textile and pharmaceutical industries and a wide range of documentary evidence, the author argues that the impact of globalization on India needs to be understood not just in terms of national policy, but also in terms of India's changing trade capacities and private sector reform"--Provided by publisher.
"This book charts the emergence of India onto the global economic stage. In the 1990s, Indian policymakers, politicians, and private sector actors were wary of the global world. By 2015 trade constituted half of India's GDP and India had become an integral part of the world order. Indian policymakers negotiate strongly at the global level and Indian companies have moved into new markets and formed new global alliances. Yet, India's economic rise at the global level was not inevitable. The process by which India is transforming is the focus of this book. I explore the economic rise of India through the actions of domestic state and private actors, who have changed what they want and how they mobilize in a very short span of time. Underlying this global emergence is a quieter revolution represented by changing trade capacities and private sector reform and transformation. The transformations described in this book have gone deep, creating Indian consent and appetite for globalization. Scholars and analysts have to document this changed reality even if they are ambivalent about the effects of India's ongoing reform trajectory, as I am"--Provided by publisher.
Machine generated contents note: 1. How global markets and rules are shaping India's rise to power -- 2. A theory of causal mechanisms and global design-in-motion -- 3. Trade, statecraft, and changing state capacity in India -- 4. Realigning interests towards global reach: changes in India's pharmaceutical sector -- 5. Mobilizing new interests and tying the State's hands: decline and revival in the textile sector -- 6. Interests in motion: private sector change in India's textile sector -- 7. Mechanisms of change within global markets -- 8. Conclusion -- Appendix -- Bibliography -- Index.
Includes bibliographical references (pages 294-320) and index.
Keywords: Globalization -- India; India -- Economic conditions -- 21st century; India -- Economic policy -- 21st century; India -- Commerce